Interventional Oncology in Immuno-Oncology Part 1: Thermal Ablation - Slovak, Ryan; Raja, Junaid; Dendy Case, Meaghan; Kim, Hyun S. (Digestive Disease Interventions, 2019)
Thermal ablation occupies a unique position among the various modalities available to treat malignancies. Initially utilized as a minimally invasive form of palliation, ablative techniques are increasingly being recognized for their role in activating an immune response. Locally destructive, but not thoroughly extirpative, thermal ablation function to generate an in situ tumor vaccine capable of stimulating and enhancing both innate and adaptive immune responses. As monotherapy, the response engendered remains therapeutically insufficient, but newer data suggests that when used as an adjuvant or neoadjuvant, ablation may synergistically boost the anticancer immune response produced by other, sequentially acting immunotherapies. The purpose of this review is to discuss the local and systemic immunological effects induced by thermal ablation. Radio frequency, microwave, and cryoablation will all be considered in addition to focused ultrasound ablation.
Keywords: immuno-oncology; cryoablation; vaccine; radio frequency ablation